IMPLEMENTASI INQUIRY-BASED LEARNING DI MASA PANDEMI (Studi Kasus di ABA St. Pignatelli Surakarta) - Muhammad Sirod; Poniman (Media Akuntansi, 2021)
This research aims to understand the extent of the students’ participation to join the lectures during the Covid-19 pandemic, that requires the lectures to be conducted through online system. In such a condition Inquary-based learning is selected as an appropriate method of learning, in which the students’ independence is needed. The researchers conducted a case study on the application of inquiry-based learning, especially in the subject of Structure-Grammar, at the English Study Program, Academy of Foreign Language St. Pignatelli Surakarta In the implementation of this method the students are expected to be autonomous learners who must be aware of themselves that they need particular knowledge and consequently, with their own accord they will find any sources from both reference-books and scientific webs. The role of the lecturer is to guide them in such a way that they master the minimum requirements. The research results show that the students of Semester II give 66.66% of positive response, and those of Semester IV 73.55%. There are more than 25 % of students who do not give positive participation to the lectures due to several obstacles, namely the lack of smart phones, adequate computers or internet access. Although the results are not so satisfying, they can be used as a reference for autonomous learning.